2009
DOI: 10.1111/j.1365-2958.2009.06945.x
|View full text |Cite
|
Sign up to set email alerts
|

BosR (BB0647) governs virulence expression in Borrelia burgdorferi

Abstract: SummaryBorrelia burgdorferi (Bb), the Lyme disease spirochaete, encodes a potential ferric uptake regulator (Fur) homologue, BosR (BB0647). Thus far, a role for BosR in Bb metabolism, gene regulation or pathogenesis has not been determined, largely due to the heretofore inability to inactivate bosR in low-passage, infectious Bb isolates. Herein, we report the generation of the first bosR-deficient mutant in a virulent strain of Bb. Whereas the bosR mutant persisted normally in ticks, the mutant was unable to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
194
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(208 citation statements)
references
References 65 publications
(103 reference statements)
13
194
1
Order By: Relevance
“…Others have reported that bosR-knockouts of B. burgdorferi are not infectious in mice (Hyde et al, 2009;Ouyang et al, 2009Ouyang et al, , 2011. Here, the WT strain B31-A3 was infectious at a dose of 20 000 spirochaetes per mouse, whereas neither of the bosR-mutant strains (L9 and K18) was infectious at this dose or at a higher dose of 100 000 spirochaetes per mouse (Table 1 and data not shown).…”
Section: Mice Become Infected By Spirochaetes Expressing Bosr But Notmentioning
confidence: 86%
See 4 more Smart Citations
“…Others have reported that bosR-knockouts of B. burgdorferi are not infectious in mice (Hyde et al, 2009;Ouyang et al, 2009Ouyang et al, , 2011. Here, the WT strain B31-A3 was infectious at a dose of 20 000 spirochaetes per mouse, whereas neither of the bosR-mutant strains (L9 and K18) was infectious at this dose or at a higher dose of 100 000 spirochaetes per mouse (Table 1 and data not shown).…”
Section: Mice Become Infected By Spirochaetes Expressing Bosr But Notmentioning
confidence: 86%
“…Strains B31-MI and 297 are infectious in mice (Ouyang et al, 2009(Ouyang et al, , 2011; however, strain ML23 lacks the lp25 linear plasmid and therefore is not infectious in mice (Hyde et al, 2009). Here, strain B31-A3 was chosen for study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations